Fame Attack The Inflation of Celebrity and its Consequences - Rojek, Chris (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The follow up to Chris Rojek's hugely successful Celebrity, this book assesses celebrity culture today. It explores how the fads, fashions and preoccupations of celebrities enter the popular lifeblood, explains what is distinctive about contemporary celebrity, and reveals the psychological, social and economic consequences of fame both upon the public and celebrities themselves. The book develops the framework for looking at celebrity culture which Rojek set out back in 2001, by showing how ascribed celebrity, achieved celebrity and celetoids overlap. The book gives a new emphasis to the role of the media and public relations in engineering fame, and the psychological consequences of celebrity - notably Narcissistic Personality Disorder and Celebrity Worship Syndrome. The book is a landmark contribution in explaining how celebrities dominate the social horizon and why we need them.